Morphofunctional changes in the internal organs of laying hens affected by chronic thiamethoxam intoxication - Dukhnytskyi, V. B.; Horalskyi, L. P.; Sokolyuk, V. M.; Gutyj, B. V.; Ishchenko, V. D.; LigominaІ. P.; Kolesnik, N. L.; Dzhmil, V. I. (Regulatory Mechanisms in Biosystems, 2024)
Insecticides play an important role in agriculture, general sanitary and veterinary practices, providing protection of the plants and yield from harmful insects and preventing the spread of arthropods which cause diseases in people and animals. Therefore, the objective of our study was to analyze the morphofunctional changes in the internal organs of laying hens affected by chronic intoxication with Actara 25 WG (thiamethoxam). Identification of the toxic action of theamethoxam was carried out in 150 day-old laying hens. The chronic intoxication with the insecticide was modeled by feeding mixed feed treated with the preparation in the doses that were calculated in mg of the active compound per 1 kg of body mass. The birds of the one group were the control and received mixed feed with no supplements. The hens of the first experimental group were given mixed feed that contained the insecticide in the dose of 360 mg/kg of body mass, and hens of the second experimental group consumed mixed feed containing the preparation in the dose of 180 mg/kg per body mass. We determined that laying hens of Experimental Group 1 had significant 1.24-fold decrease in the ventriculus and significant 1.39-fold increase in the spleen. Laying hens of Experimental Group 2 were observed to have increase in the absolute mass of the heart, measuring 1.36-fold compared with the control and 1.34-fold compared with Experimental Group 1. At the same time, the absolute masses of the spleen, liver, and ventriculus in Experimental Group 2 were 1.20, 1.46, and 1.19 times lower than in Experimental Group 1. Compared with the control, the absolute mass of the liver and ventriculus, was 1.54 and 1.48 times lower, respectively. Intake of feed with thiamethoxam by laying hens of the experimental groups led to decrease in the coefficient of relative mass of the liver and ventriculus. Those results significantly correlated with the absolute mass values of those organs, indicating the toxic impact of the insecticide on laying hens, with the digestive organs being the first to react. In Experimental Group 1 chickens, we observed dystrophic-necrotic changes in the liver, round-cell infiltration of the portal tracts; dystrophic-necrotic changes in epitheliocytes of the nephrons of the kidneys’; granular dystrophy of cardiomycetes, plethora of the capillaries, and stasis and edema of the stroma in the myocardium; pericellular edemas in the brain; mucous dystrophy, desquamation of the epithelium of the mucous membrane, decrease in lymphocytes in the lymphoid structures, and atrophy of the epithelium of the glandular structure in the stomach; hyperemia and necrosis of the villus tips, and round-cell infiltration of the crypt region in the thin intestine; and reproduction of cellular elements of the connective tissue between the crypts in the thin intestine. The insecticide in the dose of 180 mg/kg of body mass caused dystrophic-necrobiotic changes in the liver and kidneys; hyperemia and edema in the myocardium; pericellular edema, swelling, and vacuolar dystrophy of neurons in the brain; necrobiotic changes in the mucous membrane epithelioctes in the proventriculus; and deformation of the villi and edema of the mucous membrane in the small intestine.